O show da estrela: análise da campanha presidencial do PT em 2002 - Penteado, Claudio Luis de Camargo (2005)
The mass media influence on the social relations improves the elections s spetacle. The campaigns in the Mediatic Age have a new structure, more professional, in the management of activities. The political marketing is an essencial component to develop campaign strategies, inserting news actors in the electoral game. This paper studies the modern electoral campaings, with focus on the presidencial campaign of Luiz Inácio Lula da Silva in 2002. This research is a reflection about democracy and several components inside the electoral campaigns, its personages, the symbolic dimension of electoral rituals, the professionalization of the campaigns staffs, the proper politician spectacle and the definition of the campaign strategies. In this context, the Horário Gratuito de Propagada Eleitoral (HGPE) , electoral free political advertising, the most visibility place of political debate becomes the principal space of political argument. The political advertising becomes the main stage for candidats display their ideas and their images for the electores. Thus, the analysis of HGPE and the campaigns actors actions, with prominence for the perfomance of the publicity professional Duda Mendonça, allow the verification of campaign s characteristics and the persuason strategies in the Visibility Age. The adaptation of campaigns to the new technologies changed the democracy process, decreasing the popular participation, which has a new role as a spectator of political show.